2015
DOI: 10.3168/jds.2014-8110
|View full text |Cite
|
Sign up to set email alerts
|

Bio-based biodegradable film to replace the standard polyethylene cover for silage conservation

Abstract: The research was aimed at studying whether the polyethylene (PE) film currently used to cover maize silage could be replaced with bio-based biodegradable films, and at determining the effects on the fermentative and microbiological quality of the resulting silages in laboratory silo conditions. Biodegradable plastic film made in 2 different formulations, MB1 and MB2, was compared with a conventional 120-μm-thick PE film. A whole maize crop was chopped; ensiled in MB1, MB2, and PE plastic bags, 12.5kg of fresh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…). On the other hand, a great deal of attention has been paid to the search for cost‐effective alternatives to replace petroleum‐based commodity plastic films to cover silages, such as biodegradable materials with competitive mechanical properties (Borreani and Tabacco ). Biodegradable (MB) plastic films have proved to work well for conservation periods longer than 5 months in indoor conditions (Borreani and Tabacco ), but they still need to be tested in farm conditions to evaluate their ability to protect silage from the detrimental effects of moulds during conservation.…”
Section: Introductionmentioning
confidence: 99%
“…). On the other hand, a great deal of attention has been paid to the search for cost‐effective alternatives to replace petroleum‐based commodity plastic films to cover silages, such as biodegradable materials with competitive mechanical properties (Borreani and Tabacco ). Biodegradable (MB) plastic films have proved to work well for conservation periods longer than 5 months in indoor conditions (Borreani and Tabacco ), but they still need to be tested in farm conditions to evaluate their ability to protect silage from the detrimental effects of moulds during conservation.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, biodegradable film prevented maize silage from becoming unstable to the same degree as standard coating (Table 2). Similar results were obtained in studies of Borreani et al, 2010. Other experiments (Borreani et al, 2012;Borreani and Tabacco, 2015) showed better stability of maize silage covered with biodegradable film than silage covered with standard film. Denoncourt et al (2006) showed that the temperature of maize silages covered with biodegradable film based on soy protein with different hydrophobic barriers was significantly higher compared to the control silage.…”
Section: Resultsmentioning
confidence: 99%
“…However, the management of worn-out polyethylene films is a problem. Alarmingly, worn-out silage wrap is going to illegal dumping sites, being buried or burned, while the released components of polymer plastics are a serious environmental threat (Rymarz and Klecan, 2001;Majdiuk, 2002;Rutkowska et al, 2002;Denoncourt et al, 2004aDenoncourt et al, , 2004bŚwiątkowski and Walczak, 2004;Borreani and Tabacco, 2005;Laffin et al, 2005;Denoncourt et al, 2006Denoncourt et al, , 2007Borreani et al, 2014;Borreani and Tabacco, 2015). One alternative to standard coating is biodegradable film produced on the basis of natural origin polymers (chitosan, cellulose, starch, soy or whey protein, and others) or synthetic macromolecular compounds that provide food for microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…A study was conducted to determine whether the PE film could be replaced with bio-based biodegradable films [18]. A standard 120-μm-thick white-on-black PE film and two different 120-μm-thick biodegradable plastic films were used to produce the silage bags for that experiment.…”
Section: Biofilmsmentioning
confidence: 99%
“…Round bale silage requires at least 5.5 kg of plastic/ton DM. Stack silos use about 1.3 kg of plastic/ton DM, four times less than the round bale silage system [5].A study was conducted to determine whether the PE film could be replaced with bio-based biodegradable films [18]. A standard 120-μm-thick white-on-black PE film and two different 120-μm-thick biodegradable plastic films were used to produce the silage bags for that experiment.…”
mentioning
confidence: 99%